Gestational Age at Cervical Length and Fetal Fibronectin Assessment and the Incidence of Spontaneous Preterm Birth in Twins. (1st June 2015) - Fox, Nathan S.; Saltzman, Daniel H.; Fishman, Ariel; Klauser, Chad K.; Gupta, Simi; Rebarber, Andrei
Abstract : Objectives: To estimate the risk of spontaneous preterm birth in twin pregnancies based on transvaginal sonographic cervical length, fetal fibronectin (fFN) testing, and the gestational age at which these tests were performed. Methods: Women with twin pregnancies, cervical length assessment, and fFN testing between 22 weeks and 31 weeks 6 days in a single maternal‐fetal medicine practice from 2005 to 2013 were included. All testing was done on asymptomatic women on an out‐patient basis. Women with monochorionic monoamniotic twins and twin‐twin transfusion were excluded. Logistic regression analysis was used to estimate the risk of spontaneous preterm birth before 35, 32, and 28 weeks. Results: Six hundred eleven patients were included and underwent a total of 2406 cervical length measurements and 2279 fFN tests over the course of the study period. The likelihood values for spontaneous preterm birth before 35, 32, and 28 weeks were 19.1%, 6.3%, and 2.3%, respectively. The risk of spontaneous preterm birth before 35 weeks increased with a decreasing cervical length (coefficient for the log of the odds ratio [OR coefficient], −0.13; P < .01; 95% confidence interval [CI], −0.22 to −0.037), a positive fFN result (OR coefficient, 1.04; P < .01; 95% CI, 0.45 to 1.64), as well as earlier gestational ages at testing (OR coefficient, −0.214; P < .01; 95% CI, −0.33 to −0.10). Similar results were seen for spontaneous preterm birth before 32 and 28 weeks. Conclusions: In asymptomatic patients with twin pregnancies, the cervical length, fFN, and gestational age are all significantly associated with spontaneous preterm birth.